2014
DOI: 10.1007/s00220-014-2205-8
|View full text |Cite
|
Sign up to set email alerts
|

Trace Class Conditions for Functions of Schrödinger Operators

Abstract: Abstract:We consider the difference f (− + V )− f (− ) of functions of Schrödinger operators in L 2 (R d ) and provide conditions under which this difference is trace class. We are particularly interested in non-smooth functions f and in V belonging only to some L p space. This is motivated by applications in mathematical physics related to Lieb-Thirring inequalities. We show that in the particular case of Schrödinger operators the well-known sufficient conditions on f , based on a general operator theoretic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
(64 reference statements)
0
21
0
Order By: Relevance
“…In the p = 1 case, this is the result of our previous publication [5]. In the proof of Theorem 1.4, the concept of local S p -valued smoothness is important; in other words, one needs inclusions of the type GE H 0 (∆) ∈ Smooth p (H 0 ), where ∆ ⊂ (0, ∞).…”
Section: Some Applicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the p = 1 case, this is the result of our previous publication [5]. In the proof of Theorem 1.4, the concept of local S p -valued smoothness is important; in other words, one needs inclusions of the type GE H 0 (∆) ∈ Smooth p (H 0 ), where ∆ ⊂ (0, ∞).…”
Section: Some Applicationsmentioning
confidence: 94%
“…In applications to mathematical physics (see e.g. [5]), one is often interested in functions f having a cusp-type singularity on the absolutely continuous spectrum and smooth elsewhere. It is also easy to reduce the question to functions f compactly supported on (0, ∞).…”
Section: Some Applicationsmentioning
confidence: 99%
“…Another generalization that we do not pursue here is to replace the pointwise assumption (1.2) on V by an integral assumption. In [5] we showed that this was possible for p = 1.…”
Section: Introduction and Main Resultsmentioning
confidence: 89%
“…This paper is a continuation of [7], where this problem was considered in the general operator theoretic context. It is also a further development of [5], where the trace class membership of D(f ) was considered. As explained in [5] and briefly recalled in Subsection 1.6 below, this problem is in part motivated by applications to mathematical physics.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation